Fenofibrate Enhances the In Vitro Differentiation of Foxp3+ Regulatory T Cells in Mice - Zhou Zhou; Ying Liang; Yanxiang Gao; Wei Kong; Juan Feng; Xian Wang (PPAR Research)
Foxp3+ regulatory T cells (Tregs) play a critical role in maintaining immune self-tolerance. Reduced number and activity of Tregs are usually found in autoimmune and inflammatory diseases, and enhancing the differentiation of Tregs may be a promising therapeutic strategy. Some reports suggested an anti-inflammatory and anti-autoimmune potential for fenofibrate, a hypolipidemic drug used worldwide, whose lipid effects are mediated by the activation of peroxisome proliferator-activated receptor 𝛼 (PPAR𝛼). In the present paper, we found that fenofibrate dose-dependently increased transforming growth factor-𝛽 and interleukin-2-induced Treg differentiation in vitro, by 1.96-fold from 0 to 20 𝜇M (12.59±1.34% to 24.69±3.03%, 𝑃<0.05). Other PPAR𝛼 activators, WY14643 (100 𝜇M), gemfibrozil (50 𝜇M), and bezafibrate (30 𝜇M), could not enhance Treg differentiation. In addition, PPAR𝛼 could not upregulate the promoter activity of the Treg-specific transcription factor Foxp3. Fenofibrate might exert its function by enhancing Smad3 phosphorylation, a critical signal in Treg differentiation, via Akt suppression. Our work reveals a new PPAR𝛼 independent anti-inflammatory mechanism of fenofibrate in up-regulating mouse Treg differentiation.